The association of factor V leiden and prothrombin gene mutation and placenta-mediated pregnancy complications: a systematic review and meta-analysis of prospective cohort studies. - Marc A Rodger; Marisol T Betancourt; Peter Clark; Pelle G Lindqvist; Donna Dizon-Townson; Joanne Said; Uri Seligsohn; Marc Carrier; Ophira Salomon; Ian A Greer (PLoS Medicine, 2010)
Background Factor V Leiden (FVL) and prothrombin gene mutation (PGM) are common inherited thrombophilias. Retrospective studies variably suggest a link between maternal FVL/PGM and placenta-mediated pregnancy complications including pregnancy loss, small for gestational age, pre-eclampsia and placental abruption. Prospective cohort studies provide a superior methodologic design but require larger sample sizes to detect important effects. We undertook a systematic review and a meta-analysis of prospective cohort studies to estimate the association of maternal FVL or PGM carrier status and placenta-mediated pregnancy complications. Methods and findings A comprehensive search strategy was run in Medline and Embase. Inclusion criteria were: (1) prospective cohort design; (2) clearly defined outcomes including one of the following: pregnancy loss, small for gestational age, pre-eclampsia or placental abruption; (3) maternal FVL or PGM carrier status; (4) sufficient data for calculation of odds ratios (ORs). We identified 322 titles, reviewed 30 articles for inclusion and exclusion criteria, and included ten studies in the meta-analysis. The odds of pregnancy loss in women with FVL (absolute risk 4.2%) was 52% higher (OR = 1.52, 95% confidence interval [CI] 1.06-2.19) as compared with women without FVL (absolute risk 3.2%). There was no significant association between FVL and pre-eclampsia (OR = 1.23, 95% CI 0.89-1.70) or between FVL and SGA (OR = 1.0, 95% CI 0.80-1.25). PGM was not associated with pre-eclampsia (OR = 1.25, 95% CI 0.79-1.99) or SGA (OR 1.25, 95% CI 0.92-1.70). Conclusions Women with FVL appear to be at a small absolute increased risk of late pregnancy loss. Women with FVL and PGM appear not to be at increased risk of pre-eclampsia or birth of SGA infants. Please see later in the article for the Editors' Summary.